PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI (BMT) DALAM MEMBANGUN KEMANDIRIAN USAHA EKONOMI KELUARGA - MASMUROH (AL-UKHWAH - JURNAL PENGEMBANGAN MASYARAKAT ISLAM, 2024)
Developments in society certainly do not only partially occur on the religious side. There are many aspects of people's lives that can be used as objects of social change, including improvement and economic change that develops based on the independence of every human being. The Islamic boarding school in this case through the Sharia Savings and Loans Cooperative (KSPPS) BMT Al-Hikmah is aware of the challenge and then takes part in empowering every potential that exists in the community. The formulation of the problem, how is the strategy of community economic empowerment through (BMT) carried out by KSPPS BMT Al-Hikmah Bandar Lampung in Realizing Business Independence and Family Economic Resilience, and the implications of community economic development strategies in the empowerment process before and after. This type of research is descriptive qualitative, primary and secondary data sources, research subjects are 8 customers plus 2 employees, with data collection techniques interview, observation, documentation, data reduction and data analysis. The results of the empowerment strategy research conducted by KSPPS BMT Al-Hikmah through the potential of independent entrepreneurs in increasing family resilience. Through three stages, namely empowerment, capacity building, and empowerment, the implication of the strategy carried out is a solution to various problems faced by the community so as to increase income and economic welfare as well as family resilience.